Cytoreductive surgery combined with hyperthermic intraperitoneal chemotherapy and intraoperative radiation therapy in the management of gastric cancer: a 10-year single center experience - Marwan M. Alaswad; Tarek Z. Arabi; Asma S. Alshahrani; Belal N. Sabbah; Heba W. Jaamour; Abdullah A. AlOtry; Tariq W. Saleh; Ziad H. Alhosainy; Fadwa H. Elkordy; Aya I. Elnegali; Mohamed H. Tlayjeh; Firas E. Kseibi; et al. (World Journal of Surgical Oncology)
Abstract Background The rationale behind the use of HIPEC involves targeted elimination of microscopic peritoneal metastasis, a common route for GCa dissemination, thereby improving the overall survival and reducing recurrences. Moreover, the reasoning behind the use of IORT is enhanced loco-regional control and, therefore, reducing recurrence rates. Methods From February 2013 to June 2023, all GCa patients who underwent HIPEC plus IORT during surgery were included in this study. Median overall survival (OS) and disease-free (DFS) survival were used to evaluate the efficacy of this treatment strategy amongst GCa patients, along with the rate of occurrence and severity of post-operative complications associated with this treatment strategy. Results The median OS and DFS were 63 and 87 months, respectively. More than one-third of the patients in our cohort did not develop any post-operative complications. In patients who developed post-operative complications, the median number of post-operative complications was 1 (IQR 1–2). Most encountered complications were Clavien-Dindo (CD) grade II complications (33.33%) and no in-hospital mortality was observed. Conclusions This complex, multimodal treatment strategy results in a significantly prolonged OS and DFS when compared to other treatment strategies for gastric cancer patients, with no added morbidity or mortality.